Distinct actions of ancestral vinclozolin and juvenile stress on neural gene expression in the male rat - Gillette, Ross; Miller-Crews, Isaac; Skinner, Michael K.; Crews, David (Frontiers in Genetics, 2015)
Exposure to the endocrine disrupting chemical vinclozolin during gestation of an F0 generation and/or chronic restraint stress during adolescence of the F3 descendants affects behavior, physiology, and gene expression in the brain. Genes related to the networks of growth factors, signaling peptides and receptors, steroid hormone receptors and enzymes, and epigenetic related factors were measured using quantitative polymerase chain reaction via Taqman low density arrays targeting 48 genes in the central amygdaloid nucleus, medial amygdaloid nucleus, medial preoptic area, lateral hypothalamus, and the ventromedial nucleus of the hypothalamus. We found that growth factors are particularly vulnerable to ancestral exposure in the central and medial amygdala; restraint stress during adolescence affected neural growth factors in the medial amygdala. Signaling peptides were affected by both ancestral exposure and stress during adolescence primarily in hypothalamic nuclei. Steroid hormone receptors and enzymes were strongly affected by restraint stress in the medial preoptic area. Epigenetic related genes were affected by stress in the ventromedial hypothalamus and by both ancestral exposure and stress during adolescence independently in the central amygdala. It is noteworthy that the lateral hypothalamus showed no effects of either manipulation. Gene expression is discussed in the context of behavioral and physiological measures previously published.